EFFECT OF VEDIC MATHEMATICS ON ACHIEVEMENT IN MATHEMATICS AMONG FIFTH GRADE STUDENTS (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Mathematics is called mirror of our civilization. It shapes our culture as a pioneer that is why it is said, Shut out mathematics from our daily life and all civilizations come to a standstill. It is wise to base our cause for mathematics on the common sense ground of everyday experience rather than on far-reaching theoretical considerations. Moreover, to draw the inferences that mathematics is an instrument of education found to be in conformity with the need of the human mind.